Screening of potential inhibitors targeting the main protease structure of SARS-CoV-2 via molecular docking - Yang, Xinbo; Xing, Xianrong; Liu, Yirui; Zheng, Yuanjie (Frontiers in Pharmacology, 2022)
The novel coronavirus disease (COVID-19) caused by the SARS-CoV-2 virus spread rapidly to become a global pandemic. Researchers have been working to develop specific drugs to treat COVID-19. The main protease (Mpro) of the SARS-CoV-2 virus plays a pivotal role in mediating viral replication and transcription, which makes it a potential therapeutic drug target against COVID-19. In this study, a virtual drug screening method based on Mpro structure (PDB ID: 6LU7) was proposed; and 8,820 compounds collected from the DrugBank database were used for molecular docking and virtual screening. A data set containing 1,545 drug molecules, derived from compounds with a low binding free energy score in the docking experiment, was established. N-1H-indazol-5-yl-2-(6-methylpyridin-2-yl)quinazolin-4-amine, ergotamine, antrafenine, dihydroergotamine, and phthalocyanine outperformed the other compounds in binding conformation and binding free energy over the N3 inhibitor in the crystal structure. The bioactivity and ADMET properties of these five compounds were further investigated. These experimental results for five compounds suggested that they were potential therapeutics to be developed for clinical trials. To further verify the results of molecular docking, we also carried out molecular dynamics (MD) simulation on the complexes formed by the five compounds and Mpro. The five complexes showed stable affinity in terms of root mean square distance (RMSD), root mean square fluctuation (RMSF), radius of gyration (Rg), and hydrogen bond. It was further confirmed that the five compounds had potential inhibitory effects on SARS-CoV-2 Mpro.